Preparation method and application of bio-based waterborne polyurethane aerogel

The amination-modified sodium alginate reacts with polyurethane through the Aza-Michael addition reaction to form a covalent carbon-nitrogen bond, which solves the problem of insufficient compatibility and performance of bio-based polyurethane materials and realizes high-performance bio-based Water-based polyurethane airgel material.

CN119350699AActive Publication Date: 2025-01-24SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411487916.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Existing bio-based polyurethane materials do not perform well in terms of mechanical properties, flammability and solvent resistance, and the compatibility and stability of biomass and polyurethane are poor.

Method used

Through the Aza-Michael addition reaction, amination-modified sodium alginate is reacted with methacrylate-terminated polyurethane to form covalent carbon-nitrogen bonds, achieving molecular-level integration of biomass and polyurethane.

Benefits of technology

The compatibility between biomass and polyurethane is significantly improved, the mechanical properties, thermal insulation properties, flame retardant properties and self-healing properties of the material are improved, and the sustainability and adaptability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350699A_ABST
    Figure CN119350699A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polyurethane aerogel materials, and relates to a preparation method and application of bio-based waterborne polyurethane aerogel, the preparation method comprises the following steps: carrying out Aza-Michael addition reaction on amination modified sodium alginate and polyethylene glycol methacrylate terminated waterborne polyurethane, and freeze-drying to obtain the bio-based waterborne polyurethane aerogel, the prepared bio-based waterborne polyurethane aerogel can be used for a thermal insulation material, an oil stain cleaning material or a biomedical bracket. Compared with the prior art, the preparation method has the advantages that the problem of poor compatibility of polysaccharide and polyurethane in a traditional mixing method is solved, the aerogel is endowed with good biodegradability, mechanical property, adiabaticity, flame retardance and self-repairing property, and a new material choice is expected to be provided for solving the problems in the fields of energy, environment, medical treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane aerogel materials and relates to a preparation method and application of a bio-based waterborne polyurethane aerogel. Background Art

[0002] Polyurethane aerogels have attracted much attention due to their low density, excellent thermal insulation properties and mechanical strength. These unique properties make them ideal candidates for a variety of applications, such as building insulation, oil spill cleanup materials and biomedical scaffolds. However, the main raw materials (polyols and isocyanates) of traditional synthetic polyurethanes are derived from petroleum, which poses resource depletion and environmental problems. Bio-based polyurethanes are seen as sustainable alternatives, and current research focuses on replacing polyols with biomass-derived alternatives such as vegetable oils and lignin. However, polyurethanes made from vegetable oils generally exhibit poor mechanical properties, flammability and poor solvent resistance, while challenges remain for lignin due to its difficulty in separation, poor uniformity, easy aggregation, steric hindrance and low reactivity.

[0003] At present, it is common to introduce biomass such as cellulose, starch, tannic acid, etc. into polyurethane matrix by physical mixing to improve its comprehensive performance, but due to the lack of chemical bond formation, the compatibility and stability are poor. In contrast, combining biomass with polyurethane matrix through covalent bonds can achieve molecular-level integration, thereby enhancing interfacial adhesion and mechanical properties.

[0004] Sodium alginate is a natural polysaccharide that is abundant, biodegradable, non-toxic and inherently flame retardant, and is therefore considered an ideal additive for modifying polyurethane. However, due to its strong polarity, sodium alginate tends to separate from non-polar polyurethane, so achieving compatibility and uniform dispersion of the two has always been a huge challenge. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of bio-based waterborne polyurethane aerogel, by reacting amino-modified sodium alginate with methacrylate-terminated polyurethane to form a covalent carbon-nitrogen bond, so as to solve the problems of poor compatibility between biomass and polyurethane and poor overall performance in the prior art.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] Dynamic covalent bonds, due to their reversibility, give materials unique advantages such as self-repair, recyclability and adaptability, and play a key role in improving the sustainability and functionality of polyurethane. In the field of polyurethane, dynamic covalent bonds play an important role in enhancing the sustainability and functionality of materials. By introducing dynamic covalent bonds in polymer networks, polyurethanes can exhibit unique properties, such as easy repairability in response to damage, controllable degradation and the ability to adapt to environmental changes. In addition, dynamic covalent bonds can adjust material properties, including mechanical strength, flexibility and degradation kinetics, to meet specific application requirements. Among the many covalent bond construction strategies, the Aza-Michael addition reaction has the advantages of mild reaction conditions, good selectivity, reversibility, high efficiency and wide applicability, and is considered to be an effective dynamic covalent bond construction strategy. The present invention is based on the Aza-Michael addition reaction to react amino-modified sodium alginate with methacrylate-terminated polyurethane to form a covalent carbon-nitrogen bond to solve the problems of poor compatibility between biomass and polyurethane and poor overall performance in the prior art.

[0008] The first aspect of the present invention provides a method for preparing a bio-based waterborne polyurethane aerogel, comprising: subjecting amino-modified sodium alginate to an Aza-Michael addition reaction with a polyethylene glycol methacrylate-terminated waterborne polyurethane, and freeze-drying to obtain a bio-based waterborne polyurethane aerogel.

[0009] Furthermore, the preparation method of the amino-modified sodium alginate comprises: taking sodium alginate and melamine as raw materials, subjecting the raw materials to amidation reaction, dialysis and freeze-drying to obtain the alginate.

[0010] Furthermore, in the amidation reaction, the reaction temperature is 75 to 80° C. and the reaction time is 12 to 24 hours.

[0011] Furthermore, the mass ratio of the sodium alginate to melamine is 1:(1-10).

[0012] Furthermore, the degree of amino substitution of the amino-modified sodium alginate is 0.2-0.6.

[0013] Furthermore, before the amidation reaction, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are used to activate sodium alginate.

[0014] Furthermore, the mass ratio of the sodium alginate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and N-hydroxysuccinimide is 10:(4.5-5.5):(1-2); during the activation, the activation temperature is 55-60° C., and the activation time is 1-2 hours.

[0015] Furthermore, the molecular weight of the sodium alginate is 50000-400000 g / mol.

[0016] Furthermore, the molecular weight of the polyethylene glycol methacrylate terminated aqueous polyurethane is 200-2000 g / mol.

[0017] Furthermore, the preparation method of the polyethylene glycol methacrylate terminated aqueous polyurethane comprises the following steps:

[0018] 1) reacting polycaprolactone diol, dimethylol propionic acid, lysine diisocyanate and dibutyltin dilaurate (catalyst) to obtain an isocyanate-terminated polyurethane intermediate;

[0019] 2) The isocyanate-terminated polyurethane intermediate is reacted with polyethylene glycol methacrylate to obtain the product.

[0020] Furthermore, in step 1), the mass ratio of the polycaprolactone diol, dimethylol propionic acid, lysine diisocyanate and dibutyltin dilaurate is 100:(5-6):(20-30):(0.5-1.5).

[0021] Furthermore, the molecular weight of the polycaprolactone diol is 1000-5000 g / mol.

[0022] Furthermore, in step 1), in the reaction, the reaction temperature is 80-85° C. and the reaction time is 3-4 h.

[0023] Further, in step 2), the amount of polyethylene glycol methacrylate added is 75-80 g / 100 g polycaprolactone diol;

[0024] In the reaction, the reaction temperature is 50-55° C. and the reaction time is 4-6 hours.

[0025] Furthermore, the feed ratio of the amino-modified sodium alginate to the polyethylene glycol methacrylate end-capping is (0.1-10) g:(1-100) g.

[0026] Furthermore, in the reaction system of the Aza-Michael addition reaction, the content of the amino-modified sodium alginate is 1 to 10 wt.%.

[0027] Furthermore, in the Aza-Michael addition reaction, the pH of the reaction system is 8-11.

[0028] Furthermore, in the Aza-Michael addition reaction, lithium chloride is used as a pH regulator, catalyst and hygroscopic agent.

[0029] Furthermore, in the Aza-Michael addition reaction, the reaction temperature is 50 to 90° C. and the reaction time is 8 to 24 hours.

[0030] The second aspect of the present invention provides an application of a bio-based waterborne polyurethane aerogel, wherein the bio-based waterborne polyurethane aerogel has a compression strength of 0.15 to 0.98 MPa, a thermal decomposition temperature of 410 to 480°C, and a thermal conductivity of 0.021 W / m / K to 0.029 W / m / K, and can be used as thermal insulation materials (such as building insulation materials), oil pollution cleaning materials or biomedical scaffolds.

[0031] Compared with the prior art, the present invention has the following characteristics:

[0032] 1) The present invention uses the Aza-Michael addition reaction to form a covalent bond between sodium alginate and polyurethane to achieve integration at the molecular level, thereby effectively improving the compatibility of the two. In addition, the introduction of dynamic covalent Aza-Michael bonds gives the material excellent self-repairing and recyclability properties, thereby improving the adaptability and sustainability of the material.

[0033] 2) The aerogel obtained by the present invention not only has the advantages of low density and high porosity, but also has good biodegradability, mechanical properties, thermal insulation, flame retardancy and self-healing properties; at the same time, by regulating the degree of substitution of sodium alginate, the present invention can effectively regulate the mechanical properties, flame retardancy, degradation efficiency and self-healing properties of the prepared sodium alginate / polyurethane composite aerogel.

[0034] In summary, the method for preparing sodium alginate-based polyurethane aerogel based on Aza-Michael addition reaction proposed in the present invention can effectively solve the problems existing in the prior art and prepare a new type of bio-based polyurethane aerogel material with excellent performance, which has important theoretical significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the process and comprehensive performance diagram of the amino sodium alginate / polyurethane composite aerogel prepared in Example 3.

[0036] Figure 2 This is a scanning electron microscope image of the amino sodium alginate / polyurethane composite aerogel prepared in Example 3. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0038] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.

[0039] Example 1: Preparation of amination sodium alginate with different degrees of substitution

[0040] Dissolve 10g of sodium alginate in 1000ml of deionized water and adjust the pH to 5. Dissolve 4.98g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 1.52g of N-hydroxysuccinimide in 50ml of pure water, add dropwise to the above solution, and stir at 55°C for 1 hour. Then add 20g, 30g, and 40g of small molecule amination reagent melamine, react at 75°C for 12 hours, and prepare a series of amination sodium alginate with different degrees of substitution. After the reaction is completed, the solution is slowly dripped into hot methanol at 60°C for precipitation, and repeated three times to remove unreacted products. The precipitate is redissolved in ultrapure water, dialyzed for one week to remove residual salts and impurities, and finally freeze-dried to obtain amination sodium alginate powder with different degrees of substitution.

[0041] Example 2: Synthesis of polyethylene glycol methacrylate terminated polyurethane

[0042] 100.0g of polycaprolactone diol with a molecular weight of about 2000 and 5.4g of dimethylol propionic acid were vacuum dried overnight, 25g of lysine diisocyanate and 1g of dibutyltin dilaurate were added, and the isocyanate-terminated polyurethane intermediate was obtained by reaction at 80°C for 3 hours. After cooling to 50°C, 75g of polyethylene glycol methacrylate was added and the reaction was continued for 4 hours. An appropriate amount of acetone was added to reduce the viscosity, cooled to room temperature, and 4.1g of triethylamine was added dropwise for neutralization for 1 hour. Finally, the acetone was removed by rotary evaporation to obtain a polyethylene glycol methacrylate-terminated polyurethane aqueous dispersion with a solid content of 30%. By adjusting the amount of water, a polyethylene glycol methacrylate-terminated polyurethane aqueous dispersion with a solid content of 10%-30% was obtained.

[0043] Example 3: Preparation of ammoniated sodium alginate / polyurethane composite aerogels with different degrees of substitution

[0044] At 40°C, the aminated sodium alginate with different degrees of substitution prepared in Example 1 was dissolved in water, and the pH was adjusted to 9 with lithium chloride to prepare a 2wt% aqueous solution, and the polyethylene glycol methacrylate-terminated polyurethane aqueous dispersion with a solid content of 10%-30% prepared in Example 2 was added, and mixed at 60°C for 24 hours under alkaline conditions to cause Aza-Michael addition reaction. The degree of substitution and amount of sodium alginate, and the solid content and amount of the polyethylene glycol methacrylate-terminated polyurethane aqueous dispersion are listed in Table 1. After the reaction is completed, freeze drying can obtain a series of aminated sodium alginate / polyurethane aerogels with different degrees of substitution and different densities.

[0045] The aerogel sample prepared by reacting 2wt% of amino-modified sodium alginate with a substitution degree of 0.4 with a polyurethane aqueous dispersion terminated with polyethylene glycol methacrylate with a solid content of 20wt% was brittlely fractured in liquid nitrogen. A 0.1mm×0.1mm×0.1mm aerogel sample was taken and the morphology was observed by scanning electron microscopy. Figure 2 As shown in Figure 2, it can be observed that the filamentous sodium alginate and the polyurethane matrix form a three-dimensional cross-linked network structure.

[0046] Table 1

[0047]

[0048] Comparative Example 1: Preparation of pure polyurethane aerogel

[0049] Ultrapure water was added to dilute the polyethylene glycol methacrylate-terminated polyurethane aqueous dispersion with a solid content of 30% prepared in Example 2 to obtain polyethylene glycol methacrylate-terminated polyurethane aqueous dispersions with solid contents of 25%, 20%, 15%, and 10%, and freeze-dried to obtain pure polyurethane aerogels with different densities.

[0050] Comparative Example 2: Uncrosslinked Aminated Sodium Alginate / Polyurethane Aerogel

[0051] At 40°C, the 0.4 degree of substitution amination sodium alginate prepared in Example 1 was dissolved in water, and the pH was adjusted to 9 with lithium chloride to prepare a 2wt% aqueous solution, and the polyethylene glycol methacrylate-terminated polyurethane aqueous dispersion with a solid content of 20% prepared in Example 2 was added. After stirring and mixing at room temperature for 10 minutes under the condition of pH = 9, freeze-drying was performed to obtain a physically mixed amination sodium alginate / polyurethane aerogel. After testing, the density of the uncrosslinked amination sodium alginate / polyurethane aerogel was 0.08 g / cm 3 , the compressive strength is 0.16MPa and the thermal conductivity is 0.026W / m / K.

[0052] Application Example 1:

[0053] This example is used to characterize the compression properties of the materials prepared in Example 3 and Comparative Examples 1-2. The characterization method includes: using Texture Analyzer (model TA.XT plus) to perform compression testing, the applied loading rate is set to 0.5 mm / s, the aerogel sample height is 10 mm, the diameter is 14 mm, the compression strain is set to 20%, and the stress-strain value of the compression process is recorded. The compression test results are shown in Table 2.

[0054] The test results show that the compressive strength of the sodium alginate / polyurethane aerogel in the present invention is 0.15-0.98 MPa, which is comparable to other bio-based polyurethane aerogels (such as cellulose / polyurethane aerogels) and exceeds the compressive strength of polyurethane aerogels prepared from agricultural waste (0.2 MPa).

[0055] Application Example 2:

[0056] This example is used to characterize the self-healing performance of the materials prepared in Example 3 and Comparative Examples 1-2, and the characterization methods include: damage-repair and compression testing.

[0057] Test method: Aerogel samples of the same size (10 mm in height and 14 mm in diameter) were prepared, and cuts of about 3 mm in diameter and 2 mm in depth were applied to the samples to simulate damage. Subsequently, the damaged samples were heated at 60 ° C for 5 h to promote self-healing. After the self-healing was completed, the samples were subjected to compression tests in accordance with Application Example 1 and compared with the undamaged samples, so as to systematically evaluate their self-healing ability.

[0058] Self-healing test results, density is 0.09g / cm 3 The initial compressive strength of the sodium alginate / polyurethane aerogel is 0.58MPa, and the compressive strength after self-healing is 0.48MPa.

[0059] The above test results show that, thanks to the reversibility of the Aza-Michael addition reaction, the sodium alginate / polyurethane aerogel in the present invention also has excellent self-healing properties. Quantitative analysis shows that the healed aerogel can recover up to 82% of its original compressive strength.

[0060] Application Example 3:

[0061] This example is used to characterize the thermal insulation properties of the materials prepared in Example 3 and Comparative Examples 1-2, and the characterization methods include: thermal conductivity test and thermal decomposition temperature test.

[0062] Thermal conductivity test method: According to ISO 22007-2b standard, a thermal conductivity analyzer (TPS2500S, sensor model 5465) was used. The test was carried out at room temperature of 25°C. The optimized parameters for the measurement were: the heating power was set to 5mW and the duration was 5 seconds. Each sample was tested 5 times to ensure the reliability of the data, and the results were averaged.

[0063] Thermal decomposition temperature test method: According to ASTM E1131 standard, a thermogravimetric analyzer (TA, Q500 model) was used to heat the sample at a heating rate of 10°C / min in nitrogen, and the mass change of the material was recorded. The temperature at the maximum decomposition rate was defined as the thermal decomposition temperature. The adiabatic test results are shown in Table 2.

[0064] The test results show that the thermal conductivity of the pure polyurethane aerogel in the present invention is 0.03W / m / K, the thermal conductivity of the uncrosslinked sodium alginate / polyurethane aerogel is 0.026W / m / K, and the thermal conductivity of the crosslinked sodium alginate / polyurethane composite aerogel is 0.022W / m / K, which is significantly lower than the traditional polyurethane aerogel and other common thermal insulation materials, such as aramid nanofiber aerogel (0.031W / m / K), silicon aerogel (0.026W / m / K) and ceramic composite silica aerogel (0.042W / m / K), indicating that it has potential advantages in thermal insulation applications. The thermal decomposition temperature of the pure polyurethane aerogel in the present invention is 330°C, the thermal decomposition temperature of the uncrosslinked sodium alginate / polyurethane composite aerogel is 400°C, and the thermal decomposition temperature of the crosslinked sodium alginate / polyurethane composite aerogel is 450°C, which is significantly higher than common thermal insulation materials such as urea-formaldehyde foam (317°C) and phenolic foam (400°C).

[0065] Application Example 4:

[0066] This example is used to characterize the combustion performance of the materials prepared in Example 1 and Comparative Examples 1-2, and the characterization method includes: limiting oxygen index test.

[0067] Test method: Use JF-3 oxygen index meter for testing. Sample size is 150mm×10mm×10mm. According to ASTM D2863-19 standard, the sample needs to be conditioned for 24 hours at a temperature of 23±2℃ and a relative humidity of 50±5% before testing. Record the minimum oxygen concentration required for the sample to burn 50mm, and repeat the test five times to get the average value.

[0068] The combustion test results are shown in Table 2. The limiting oxygen index of pure polyurethane aerogel is 17.1%, the limiting oxygen index of uncrosslinked sodium alginate / polyurethane aerogel is 25.8%, and the limiting oxygen index of crosslinked sodium alginate / polyurethane composite aerogel is 28.5%.

[0069] The combustion test shows that the limiting oxygen index value of the sodium alginate / polyurethane composite material in the present invention is relatively high, surpassing that of the palm-based polyurethane composite material (22.1%), and is comparable to the performance of some polyurethane composite materials with added flame retardants (26.1%), further indicating its application prospect as a potential bio-based flame retardant material.

[0070] Table 2

[0071]

[0072] In summary, the sodium alginate / polyurethane composite aerogel of the present invention exhibits significantly superior performance compared to conventional polyurethane aerogels, specifically a lower density (0.02-0.22 g / cm 3 ), higher compression strength (0.15-0.98MPa), higher decomposition temperature (410℃-480℃), lower thermal conductivity (0.021W / m / K-0.029W / m / K) and better self-healing efficiency (80%-95%), while in comparison, the compression strength of traditional polyurethane aerogel is only 0.15MPa, the decomposition temperature is 330℃, and the thermal conductivity is 0.031W / m / K. In addition, the present invention can effectively regulate the self-healing, recyclability, biodegradability and flame retardant properties of the composite aerogel by adjusting the degree of amino substitution of sodium alginate. Therefore, the bio-based waterborne polyurethane aerogel provided by the present invention has broad application prospects in multiple fields, and is expected to provide new material options for solving problems in the fields of energy, environment, and medical care.

[0073] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a bio-based waterborne polyurethane aerogel, characterized in that: include: The amino-modified sodium alginate and the polyethylene glycol methacrylate-terminated waterborne polyurethane were subjected to Aza-Michael addition reaction and freeze-dried to obtain the bio-based waterborne polyurethane aerogel.

2. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 1, characterized in that: The preparation method of the amino-modified sodium alginate comprises: taking sodium alginate and melamine as raw materials, performing amidation reaction, dialysis and freeze-drying to obtain the alginate.

3. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 2, characterized in that: In the amidation reaction, the reaction temperature is 75-80° C., and the reaction time is 12-24 hours; the mass ratio of the sodium alginate to the melamine is 1:(1-10).

4. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 2, characterized in that: Before the amidation reaction, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are used to activate the sodium alginate.

5. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 4, characterized in that: The mass ratio of the sodium alginate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide is 10:(4.5-5.5):(1-2); during the activation, the activation temperature is 55-60° C. and the activation time is 1-2 hours.

6. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 1, characterized in that: The preparation method of the polyethylene glycol methacrylate terminated aqueous polyurethane comprises the following steps: 1) reacting polycaprolactone diol, dimethylol propionic acid, lysine diisocyanate and dibutyltin dilaurate to obtain an isocyanate-terminated polyurethane intermediate; 2) The isocyanate-terminated polyurethane intermediate is reacted with polyethylene glycol methacrylate to obtain the product.

7. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 6, characterized in that: In step 1), the mass ratio of the polycaprolactone diol, dimethylol propionic acid, lysine diisocyanate and dibutyltin dilaurate is 100:(5-6):(20-30):(0.5-1.5); In the reaction, the reaction temperature is 80-85° C. and the reaction time is 3-4 h.

8. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 6, characterized in that: In step 2), the amount of polyethylene glycol methacrylate added is 75-80 g / 100 g polycaprolactone diol; In the reaction, the reaction temperature is 50-55° C. and the reaction time is 4-6 hours.

9. The method for preparing the bio-based waterborne polyurethane aerogel according to claim 1, characterized in that: The feeding ratio of the amino-modified sodium alginate to the polyethylene glycol methacrylate end-capping is (0.1-10) g:(1-100) g; In the Aza-Michael addition reaction, the reaction temperature is 50 to 90° C. and the reaction time is 8 to 24 hours.

10. An application of the bio-based waterborne polyurethane aerogel prepared by the method according to any one of claims 1 to 9, characterized in that: The bio-based waterborne polyurethane aerogel is used for thermal insulation materials or biomedical stents.

Citation Information

Patent Citations

  • Sodium alginate-waterborne polyurethane elastomer and preparation method thereof

    CN108794722A

  • Biomass aerogel flame-retardant polyurethane flexible foam and preparation method thereof

    CN109971031A

  • Preparation method of ultraviolet-curing rapid hemostatic hydrogel material and hemostatic hydrogel material prepared by same

    CN114984297A

  • Method for preparing melamino-formaldehyde resin aerogel through normal-pressure drying

    CN116655998A

  • Application of modified bioactive glass in preparation of multifunctional polyurethane hydrogel

    CN118255962A

Cited By

  • Alginate-based carbon aerogel for fuel cell and preparation method of alginate-based carbon aerogel

    CN122482442A